Efficiency of playback for assessing the occurrence of five bird species in Brazilian Atlantic Forest fragments - Boscolo,Danilo (2006)
Playback of bird songs is a useful technique for species detection; however, this method is usually not standardized. We tested playback efficiency for five Atlantic Forest birds (White-browed Warbler Basileuterus leucoblepharus, Giant Antshrike Batara cinerea, Swallow-tailed Manakin Chiroxiphia caudata, Whiteshouldered Fire-eye Pyriglena leucoptera and Surucua Trogon Trogon surrucura) for different time of the day, season of the year and species abundance at the Morro Grande Forest Reserve (South-eastern Brazil) and at thirteen forest fragments in a nearby landscape. Vocalizations were broadcasted monthly at sunrise, noon and sunset, during one year. For B. leucoblepharus, C. caudata and T. surrucura, sunrise and noon were more efficient than sunset. Batara cinerea presented higher efficiency from July to October. Playback expanded the favourable period for avifaunal surveys in tropical forest, usually restricted to early morning in the breeding season. The playback was efficient in detecting the presence of all species when the abundance was not too low. But only B. leucoblepharus and T. surrucura showed abundance values significantly related to this efficiency. The present study provided a precise indication of the best daily and seasonal periods and a confidence interval to maximize the efficiency of playback to detect the occurrence of these forest species.